Capital structure and determinants of capital structure, before, during and after the 2008 financial crisis: A South African study - Ntshobane, Gcobisa (Department of Finance and Tax, 2021)
This study examines the effects of 2007/8 financial crisis on capital structure determinants of Johannesburg Stock Exchange (JSE) listed companies in South Africa. Data extracted from INET BFA Expert database was analyzed using regression models on the correlation between the leverage and company size, growth, profitability, tangibility, liquidity, non-debt tax shield along with Ordinary Least Squares based on the sample of JSE listed companies for the period of 2004 to 2013. The study examined two industries namely, Real estate and Retail industry. The results show that size, tangibility, profitability and liquidity have significant impact on the capital structure before, during and after financial crisis. Growth results were inconsistent over the period under review, and non-debt tax shield was found to be statistically insignificant. The study also shows that the 2007/8 had statistical significance on the capital structure of the listed companies in South Africa.